A Remark on the Fractional Integral Operators and the Image Formulas of Generalized Lommel–Wright Function - Agarwal, Ritu; Jain, Sonal; Agarwal, Ravi P.; Baleanu, Dumitru (Frontiers in Physics, 2018)
In this paper, the operators of fractional integration introduced by Marichev-Saigo-Maeda involving Appell's function F3(·) are applied, and several new image formulas of generalized Lommel–Wright function are established. Also, by implementing some integral transforms on the resulting formulas, few more image formulas have been presented. We can conclude that all derived results in our work generalize numerous well-known results and are capable of yielding a number of applications in the theory of special functions. Primary: 44A20 Transforms of special functions; 65R10 For numerical methods; 26A33 Fractional derivatives and integrals; Secondary: 33C20 Generalized hypergeometric series, pFq; 33E50 Special functions in characteristic p (gamma functions, etc.); 2010 AMS classification by MathSciNet